Laparoscopic Radical Antegrade Modular Pancreatosplenectomy (RAMPS) Technique: Toward the Standardization of the Technique (With Video). Issue 4 (August 2020) - Ielpo, Benedetto; Pietrasz, Daniel; Torrent, Laia; Tortajada, Pauline; Ciacio, Oriana; Pittau, Gabriella; Adam, Rene; Sa Cunha, Antonio
Abstract : Laparoscopic left pancreatectomy for pancreatic cancer has increased worldwide over the last decade. However, this procedure is technically challenging compared with traditional laparoscopic left pancreatectomy and still needs to be better standardized. On this video, we describe the standardization of the technique at our center, highlighting some technical tips and tricks. Abstract : Supplemental Digital Content is available in the text.